2018
DOI: 10.1002/lio2.227
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms in cervical vertigo

Abstract: Objective To use a unique, 41‐question survey to identify patient features distinguishing cervical vertigo from vestibular causes of vertigo and vestibular migraine. Methods In this study, a unique, 41‐question survey was administered to 48 patients diagnosed with cervical vertigo (n = 16), migraine (n = 16), and vestibular vertigo (eg, unilateral vestibular paresis, Meniere's disease) (n = 16) to test the hypothesis that a set of distinct symptoms can characterize cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
3
21
0
7
Order By: Relevance
“…The semicircular canals are constructed for precise and rapid detection of head rotations (Halterman, ; Schubert & Shephard, ) and thus, a deficit or damage to this system often manifests as a strong sense of spinning, which is often of acute onset (Magnusson & Karlberg, ). Contrary to this, dizziness of cervical origin is usually thought to manifest itself as an unpleasant or vague feeling of dizziness without a strong sense of rotation (Thompson‐Harvey & Hain, ). However, there is a lack of clinical studies reporting descriptions of dizziness of suspected cervical origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The semicircular canals are constructed for precise and rapid detection of head rotations (Halterman, ; Schubert & Shephard, ) and thus, a deficit or damage to this system often manifests as a strong sense of spinning, which is often of acute onset (Magnusson & Karlberg, ). Contrary to this, dizziness of cervical origin is usually thought to manifest itself as an unpleasant or vague feeling of dizziness without a strong sense of rotation (Thompson‐Harvey & Hain, ). However, there is a lack of clinical studies reporting descriptions of dizziness of suspected cervical origin.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of clinical studies reporting descriptions of dizziness of suspected cervical origin. Patients with cervicogenic dizziness seem to report a feeling of drunkenness/light‐headedness more often than patients with benign paroxysmal positional vertigo (L'Heureux‐Lebeau, Godbout, Berbiche, & Saliba, ), and less likely to report spinning vertigo than patients with benign paroxysmal positional vertigo and other vestibular disorders (L'Heureux‐Lebeau, Godbout, Berbiche, & Saliba, ; Thompson‐Harvey & Hain, ). Interestingly, this study found that both neck pain groups were more likely to report light‐headedness, which has been suggested to be related to neck‐related dizziness (Devaraja, ; Wrisley, Sparto, Whitney, & Furman, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adicionalmente, para el diagnóstico del mareo cervicogénico también puede llevarse a cabo a través de la realización de las pruebas de rango de movimiento cervical (rotación, cabeceo sagital y movimientos coronales) para observar si existe desencadenamiento de la sensación de mareo en determinadas posiciones (Whitman, 2018) Es decir que las pruebas de evaluación vestibular resultan ser de verdadera utilidad para abordar el mareo cervical desde su etapa diagnóstica, no obstante, su implementación solo permite eliminar otras posibles causas del mareo, lo que ratifica el hecho de que en la actualidad el diagnóstico del mareo cervicogénico se realice a través de métodos de exclusión (Reiley, Vickory, Funderburg, Cesario, & Clendaniel, 2017) . Adicionalmente, (Reid S. , Callister, Katekar, & Treleaven, 2017 b) proponen que también es importante realizar una anamnesis exhaustiva, con el propósito de identificar duración, tipo y si se trata de un mareo rotatorio, pues una de las principales dificultades del diagnóstico del vértigo cervical es que su sintomatología puede solaparse con otras entidades patológicas (Thompson-Harvey & Hain, 2019) En los casos en que los mareos se han producido posterior a un traumatismo cerrado de cuello, (Reiley, Vickory, Funderburg, Cesario, & Clendaniel, 2017), manifiestan que se debe realizar evaluación del sistema vestibular, siempre y cuando no exista afectación neurológica o de las estructuras óseas de la columna cervical, lo que significa que la valoración a través de pruebas vestibulares se debe realizar en pacientes con mareos atribuidos a traumas cerrados de cuello o a patología degenerativa cervical para descartar compromiso vestibular.…”
Section: Implementación De Las Pruebas Vestibulares En El Vértigo De unclassified
“…Cervicogenic dizziness can result in a variety of coexisting symptoms such as unsteadiness, lightheadedness, perceptions of spinning, nausea, and general disorientation [8]. Thompson-Harvey and Hain reported that patients with cervical vertigo have neck pain (94%), true vertigo (27%), and headache (50%) [9]. These disabling symptoms may have significant psychological repercussions which can lead to anxiety, depression, and difficulty completing activities of daily living and occupational duties [8].…”
Section: Introductionmentioning
confidence: 99%